2016
DOI: 10.7314/apjcp.2016.17.4.2105
|View full text |Cite
|
Sign up to set email alerts
|

Factors Delaying Presentation of Sudanese Breast Cancer Patients: an Analysis Using Andersen's Model

Abstract: Purpose: A multicenter, observational, cross-sectional study was conducted to assess factors delaying presentation of breast cancer cases. Materials and Methods: Data were collected from a pair of highly specialized referral centers, both located in the center of the Sudanese capital, Khartoum. For a total of 153 eligible respondents, durations of delay, clinicodemographic factors and reasons of referral were collected from our respondents through self-administered questionnaires. Logistic regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Many studies in sub-Saharan Africa have described significant delays to presentation. [6,10,13,19,[22][23][24][25] In the present study, the average time to presentation at the breast clinic was 2 months from the time of noticing any symptoms, which is shorter than in many other African studies, where delay can be measured in years, but comparable to study groups from urban populations in other upper-middle-income countries worldwide. In Malaysia, 56% of patients presented over 3 months from the time of noticing symptoms; [26] in Brazil this figure was 70% [27] and in Mexico it was 73.7%.…”
Section: Researchmentioning
confidence: 54%
See 2 more Smart Citations
“…Many studies in sub-Saharan Africa have described significant delays to presentation. [6,10,13,19,[22][23][24][25] In the present study, the average time to presentation at the breast clinic was 2 months from the time of noticing any symptoms, which is shorter than in many other African studies, where delay can be measured in years, but comparable to study groups from urban populations in other upper-middle-income countries worldwide. In Malaysia, 56% of patients presented over 3 months from the time of noticing symptoms; [26] in Brazil this figure was 70% [27] and in Mexico it was 73.7%.…”
Section: Researchmentioning
confidence: 54%
“…While small studies from various parts of the world suggest that patient-related delay to care is common, [6][7][8][9][10] the characteristics of delay and its relationship to stage of breast cancer presentation are still poorly documented, especially in southern Africa. Older studies have cited fear of mastectomy and adherence to traditional healing as causes of delay, [7,11,12] but more recent studies and systematic reviews show extremes of age (the youngest and oldest patients being most affected), marital status, education and income as being of most importance.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest study conducted in Ghana identified low level of education and delayed care-seeking behavior as risk factors for presenting with tumors larger than 5 cm [8]. Similarly, other smaller studies have identified limited knowledge [11][12][13][14][15][16], stigma associated with a cancer diagnosis, lack of social and financial support, and seeking alternative treatment from traditional healers as risk factors for delayed presentation [11][12][13][14][15][16][17][18][19][20][21][22][23]. Although the current literature identifies several factors associated with delayed breast cancer presentation and the need for breast education as a cornerstone for increasing awareness, more research is needed to understand the information gaps specific to the sociocultural setting.…”
Section: Introductionmentioning
confidence: 99%
“…[19] For people with potential symptoms of cancer, the journey to cancer diagnosis is complex and influenced by a multitude of factors including knowledge and awareness of cancer symptoms, symptom experiences, risk perception, and psychological, sociocultural and health system barriers to healthcare. [21][22][23][24][25][26][27][28][29][30][31] The Model of Pathways to Treatment provides a useful research framework to understand patient journeys, as it takes into account the complicated and dynamic nature of help-seeking behaviour. [32,33] By increasing understanding of the factors influencing the key events in the pathway to care, the model can be used to identify targets for interventions in order to encourage early detection, presentation and treatment.…”
Section: Editorialmentioning
confidence: 99%